Peranan Edukasi Kesehatan Reproduksi Pada Remaja - Eko Bambang (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Health in adolescence is an important aspect in an individual's life cycle. This period is the time when individuals begin to learn and have functional abilities and health. In terms of health, this period is an important period for reproductive health and the initial formation of healthy living behavior. Based on data from the 2010 Population Census, the group of teenagers aged 10-19 years has a proportion of 18.3% of the total population of Indonesia or around 43.5 million people. The large population of teenagers is an asset and potential for the nation in the future, therefore growth and development must proceed positively and be free from various threatening problems, including reproductive health problems.